212k views
4 votes
What is the solution to this equation? 6x + 10 – 2x = 7 + 23

2 Answers

7 votes
6x + 10 - 2x = 7 + 23
4x + 10 = 30
4x = 20
x = 5
User Jack Miao
by
5.6k points
4 votes

Solve:

6x + 10 – 2x = 7 + 23

Let's solve your equation step-by-step.

6x + 10 − 2x = 7 + 23

Step 1: Simplify both sides of the equation.

6x + 10 − 2x = 7 + 23

6x + 10 + −2x = 7 + 23

(6x + −2x) + (10) = (7 + 23) (Combine Like Terms):

4x + 10 = 30

4x + 10 = 30

Step 2: Subtract 10 from both sides.

4x + 10 − 10 = 30 − 10

4x = 20

Step 3: Divide both sides by 4.

4x / 4 = 20 / 4

x = 5

Therefore; Solution/Answer; 6x + 10 – 2x = 7 + 23; Answer: ( x = 5 )

Hope that helps!!!! : )

User Luvjungle
by
5.1k points